Desain Prototype Teknologi Automatic Surface Treatmen Untuk Meningkatkan Ketahanan Jalan Rel Kereta Api - Wirawan, Willy Artha; Wahjono, Hari Boedi; Rozaq, Fadli (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2020)
The purpose of this research is to design a prototype tool to improve the resistance of railroad tracks. The method in this study was carried out with the concept of surface treatment theory, then described using solidwork software in the form of prototype design. As a validation of the prototype design, preliminary research was carried out by giving heat treatment to the railroad tracks by utilizing the oxy-acetylene gas neutral flame and quenching quickly. Furthermore the railroad tracks were tested for hardness and microstructure. Rail test results are known to occur an increase in the value of hardness by 30 VHN and changes in the martensitic microstructure.